The reclamation of the surface layer of mining landscapes of Kryvyi Rih landscape technical system - Koptieva , T. S. (Man and Environment. Issues of Neoecology, 2023)
Purpose. To investigate the reclamation of the surface layer of mining landscapes of Kryvyi Rih landscape technical system on the example of Shymaniv and Hanniv dumps. Methods. Historical analysis, comparative, cartographic, method of anthropogenic landscape forecasting. Results. It has been determined that Shymaniv dump was created by the Southern Mining and Processing Plant in 1960–1967, belongs to mixed dumps, was formed by automobile tailings resulted into tiers with a leveled and plateau-like surface. The dump in the geological structure has a lower accumulative microstrip, which consists of crystalline rocks that are not involved into development, limestones, loess-like loams; the middle accumulative – denudation microstrip, which is characterized by crushed stone, sand, stone blocks and the upper denudation microstrip, which is represented by blocks and granites. The dump reclaimed and has favorable conditions for the germination of vegetation. By example of the Hanniv dump the possibility of rational use of the surface layer of mining landscapes was considered. The Hanniv dump is a mixed dump with its height of 90 m, partially reclaimed. A gradual biological reclamation technology is proposed for the rapid adaptation of plants to unusual terrain and the improvement of disturbed lands. Maps and technology of biological reclamation have been developed, which reflect the surface layer of mining landscapes of Kryvyi Rih landscape technical system. Conclusions. The reclamation of the surface layer of mining landscapes of Kryvyi Rih landscape technical system exists and needs a detailed study in order to prevent the degradation of disturbed lands due to the action of the mining industry. On the example of Shymaniv and Hanniv dumps the reclamation of the surface layer of mining landscapes has been investigated, the history of the dumps has been determined, the geological - geomorphological, hydrological, climatic, soil - biotic processes that influenced the favorable formation of the reclamation of the surface layer of the dumps have been substantiated, and a gradual biological reclamation technology has been proposed on the example of Hanniv dump.